Analisis Komparatif Produk Cicil Emas di Bank Syariah Indonesia dalam Prespektif Hukum Islam dan Hukum Positif - Nurjeda Komalasari; Iksan Iksan; Muhammad Amin (CV Rewang Rencang, 2025)
This article discusses a comparative analysis of the gold installment product offered by Bank Syariah Indonesia (BSI) from the perspective of Islamic law and Indonesian positive law. The gold installment product is a form of innovation in Islamic financial services that combines Islamic principles with modern market needs through the murābaḥah contract scheme. In Islamic law, transactions of usurious commodities such as gold require strict requirements to avoid usury and gharar. Meanwhile, in the Indonesian positive legal system, the legality of this product is determined by compliance with formal regulations, including Law Number 21 of 2008 concerning Islamic Banking and supervision by the Financial Services Authority (OJK). This study uses a normative approach with a descriptive-analytical method to examine the meeting point and potential disharmony between the two legal systems. The results of the analysis show that there is consistency in principle in the aspects of prudence, transparency, and the prohibition of usury, but there are still gaps in implementation, especially if the contract is only carried out formally without considering the substance of ownership and the validity of the transaction according to sharia. Therefore, the synergy between DSN-MUI fatwas, OJK regulations, and Islamic banking operational practices needs to be strengthened to ensure substantive compliance with the two applicable legal systems.